A Review of Psycholinguistic Approaches in Teaching English as a Foreign Language - Rana Mai Zuhra; Adinda Dea Nazhira; Divo Pratama Pasaribu; Yani Lubis (Lembaga Pengembangan Kinerja Dosen, 2024)
This study reviews the integration of psycholinguistic principles into the teaching of English as a foreign language (EFL) by synthesizing insights from 25 selected empirical and theoretical articles. Using a systematic literature review approach, the research identifies key cognitive and affective mechanisms that shape how learners process, store, and produce linguistic information in EFL contexts. The findings highlight the importance of working memory, input processing, lexical access, automatization, motivation, and learner anxiety in determining language-learning outcomes. Psycholinguistically informed strategies such as structured input, guided noticing, semantic mapping, spaced repetition, and fluency-building activities are shown to enhance learners’ comprehension, retention, and communicative performance. The review also underscores the growing relevance of technology-based tools that support cognitive processing and provide adaptive learning opportunities. Overall, this study concludes that psycholinguistics offers a strong conceptual foundation for designing effective, learner-centered EFL instruction and recommends more classroom-based research to examine the practical impact of these approaches in diverse educational settings.